PLANNING AND DEVELOPMENT OF THE RAVAGED LANDS OF THE NAMANGAN ADYRS - Dadakhodjaev Anvar (International Journal of Innovations in Engineering Research and Technology, 2023)
Primary reclamation of ravine lands. We studied the totality of the agro-forest, reclamation and hydro-reclamation measures for the radical reclamation of the valley’s ravine lands.